Mekanisme Sukuk Hijau: Tinjauan Regulasi dan Praktik di Indonesia - BatuBara, Rini Wahyuni; Lubis, MHD Reski Padly; Kholidatun Napisah; Ferdiansyah; Paisal Rahmat (Universitas Muhammadiyah Surabaya, 2026)
Green sukuk is an Islamic financial instrument used to finance environmentally friendly projects in supporting sustainable development. Indonesia became a pioneer in issuing green sukuk in 2018, reflecting its commitment to integrating economic and environmental aspects. This study aims to analyze the mechanisms, regulations, and implementation of green sukuk in Indonesia. The method used is a literature study with a descriptive qualitative approach. The results show that green sukuk plays a strategic role in financing green infrastructure and supporting the achievement of sustainable development goals. However, its development still faces challenges such as limited human resources, low public literacy, and risks associated with environmental projects. Therefore, stronger regulations and increased education are needed to support the optimal development of green sukuk.